Fas-Induced Apoptosis of Renal Cell Carcinoma is Mediated by Apoptosis Signal-Regulating Kinase 1 via Mitochondrial Damage-Dependent Caspase-8 Activation - Mohamed Hassan; Oliver Feyen; Edgar Grinstein (Cellular Oncology)
Renal cell carcinoma (RCC) is a prototype of a chemo refractory tumour. It remains the most lethal of the common urologic cancers and is highly resistant to conventional therapy. Here, we confirmed the efficiency of anti-Fas monoclonal antibody (CH11) as alternative therapeutic approach for the treatment of RCC and investigated the molecular mechanism(s), whereby CH11 induces apoptosis of RCC cells. The present study shows an essential role for apoptosis signal-regulating kinase 1 (ASK1), together with both c-jun-N-terminal kinase (JNK) and p38 pathways, and caspase-8 in this process. Furthermore, CH11-dependent induction of the ASK1–JNK/p38 pathways was found to activate the transcription factors AP-1 and ATF-2, and FADD-caspase-8-Bid signalling, resulting in the translocation of both Bax and Bak proteins, and subsequently mitochondrial dysregulation that is characterized by the loss of mitochondrial membrane potential (ΔΨm), cytochrome c release and cleavage of caspase-9, caspase-3 and PARP. Thus, the described molecular mechanisms of CH11-induced apoptosis suggest the reliability of Fas activation as an alternative therapeutic approach for the treatment of patients with advanced renal cell carcinoma.